2019
DOI: 10.1051/0004-6361/201935881
|View full text |Cite
|
Sign up to set email alerts
|

Relations between phenomenological and physical parameters in the hot coronae of AGNs computed with the MoCA code

Abstract: Context. The primary X-ray emission in active galactic nuclei (AGNs) is widely believed to be due to Comptonisation of the thermal radiation from the accretion disc in a corona of hot electrons. The resulting spectra can, in first approximation, be modelled with a cut-off power law, the photon index and the high-energy roll-over encoding information on the physical properties of the X-ray-emitting region. The photon index and the high-energy curvature of AGNs (Γ, E c ) have been largely studied since the launc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
50
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 48 publications
(56 citation statements)
references
References 59 publications
6
50
0
Order By: Relevance
“…The energy cutoff was usually estimated by the temperature of the hot corona with a relation, E cut ∼ (2-3)kT e (Petrucci et al 2001). Although Middei et al (2019) reported that this relationship works only for low temperatures, this correction should therefore be appropriate for the warm corona model. Given that the Eddington ratio of ESO 362-G18 is not very large ( m 0.015), the low electron temperature derived with Model A is in conflict with the trend found by Ricci et al (2018), while our result of a higher coronal temperature in the relativistic reflection scenario (Model B) is compatible with their analysis.…”
Section: Physical Properties Of the Warm Corona Modelmentioning
confidence: 99%
“…The energy cutoff was usually estimated by the temperature of the hot corona with a relation, E cut ∼ (2-3)kT e (Petrucci et al 2001). Although Middei et al (2019) reported that this relationship works only for low temperatures, this correction should therefore be appropriate for the warm corona model. Given that the Eddington ratio of ESO 362-G18 is not very large ( m 0.015), the low electron temperature derived with Model A is in conflict with the trend found by Ricci et al (2018), while our result of a higher coronal temperature in the relativistic reflection scenario (Model B) is compatible with their analysis.…”
Section: Physical Properties Of the Warm Corona Modelmentioning
confidence: 99%
“…We construct the continuous relation above based on two commonly assumed limiting cases for kT e , E cut 2 for t  1 e and E cut 3 for t 1 e  (e.g., Shapiro et al 1976), noting that more realistic coronal models cover a wider range of scaling factors (Middei et al 2019). kT e , Γ, and τ e are related via an approximate expression derived for a plane-parallel corona and formally valid for t  1 e (Zdziarski 1985;Petrucci et al 2001):…”
Section: Exclusion Of Potentially Degenerate Constraintsmentioning
confidence: 99%
“…However, it is not an accurate representation of the AGN coronal spectrum (e.g., Fabian et al 2015;Lubiński et al 2016;Niedźwiecki et al 2019). Although the phenomenological parameter E cut may be approximately converted to a coronal temperature under certain assumptions (Middei et al 2019), the proper way to characterize the physical parameters of obscured AGN coronae is to directly employ more parameter and is likely spurious. From fits with R pex fixed at 0, 1, and 2, they derive E cut in the range of 40-90 keV, all of which correspond to τ e >3.…”
Section: Limitations and Future Workmentioning
confidence: 99%
See 1 more Smart Citation
“…These high energy cut-offs can then be used to estimate the coronal temperature (e.g. Middei et al 2019) which in turn allows for testing whether pair-production is important for these systems or not (Fabian et al 2015). For a thermal plasma, there is a maximum threshold temperature beyond which a pair cascade would occur and this threshold depends on the compactness parameter l = Lσ T /Rm e c 3 , where L is the luminosity and R is the size of the corona (Svensson 1984;Zdziarski 1985).…”
Section: Introductionmentioning
confidence: 99%